Основы построения зенитных ракетных комплексов учебное пособие - Байдаков В. И. Владимир Иванович; Ленский В. Н. Владимир Николаевич; Карманов П. В. Павел Владимирович; Акулов И. Е. Игорь Евгеньевич; Васильев А. Г. Анатолий Григорьевич (Томск, Изд-во ТПУ, 2021)
Заглавие с титульного экрана